1993
DOI: 10.3143/geriatrics.30.964
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Impacted Bile Duct Stone in the Elderly.

Abstract: Acute cholangitis due to impacted bile duct stone is sometimes fatal and require prompt bile duct decompression. Particularly, AOSC (acute obstructive suppurative cholangitis) is the most serious form of bacterial cholangitis and its prognosis is ususally very poor when treated conservatively. We have been treated impacted bile duct stones by decompressing the duct endoscopically. Here, we report the characteristics of our elderly patients with impacted bile duct stones who received urgent decompression treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…It has been reported that the mortality rate of acute cholangitis was higher than 50 % before 1980, 10-30 % in 1981-1990s, and 2.7-10 % after 2000 [42,45,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. Such differences in mortality rate are assumed to have arisen from differences in severity and diagnostic criteria for the accumulated cases.…”
Section: Other Etiologies Of Acute Cholangitismentioning
confidence: 99%
“…It has been reported that the mortality rate of acute cholangitis was higher than 50 % before 1980, 10-30 % in 1981-1990s, and 2.7-10 % after 2000 [42,45,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. Such differences in mortality rate are assumed to have arisen from differences in severity and diagnostic criteria for the accumulated cases.…”
Section: Other Etiologies Of Acute Cholangitismentioning
confidence: 99%
“…The reported mortality of acute cholangitis varies from 2.5% to 65% (Table 4). The mortality rate before 1980 was 50%,, and after 1980 it was 10%–30% . Such differences in mortality are probably attributable to differences in early diagnosis and improved supportive treatment.…”
Section: Acute Cholangitismentioning
confidence: 99%
“…The major cause of death in acute cholangitis is multiple organ failure with irreversible shock, and mortality rates have not significantly improved over the years . Causes of death in patients who survive the acute stage of cholangitis include multiple organ failure, heart failure, and pneumonia …”
Section: Acute Cholangitismentioning
confidence: 99%
See 2 more Smart Citations